Direct imaging of the circular chromosome in a live bacterium - Wu, Fabai (Nat Commun, 2019)
Although the physical properties of chromosomes, including their morphology, mechanics, and dynamics are crucial for their biological function, many basic questions remain unresolved. Here we directly image the circular chromosome in live E. coli with a broadened cell shape. We find that it exhibits a torus topology with, on average, a lower-density origin of replication and an ultrathin flexible string of DNA at the terminus of replication. At the single-cell level, the torus is strikingly heterogeneous, with blob-like Mbp-size domains that undergo major dynamic rearrangements, splitting and merging at a minute timescale. Our data show a domain organization underlying the chromosome structure of E. coli, where MatP proteins induce site-specific persistent domain boundaries at Ori/Ter, while transcription regulators HU and Fis induce weaker transient domain boundaries throughout the genome. These findings provide an architectural basis for the understanding of the dynamic spatial organization of bacterial genomes in live cells.